Emergent Ferromagnetism with Fermi-Liquid Behavior in Proton Intercalated CaRuO 3 - Shen, Shengchun; Li, Zhuolu; Tian, Zijun; Luo, Weidong; Okamoto, Satoshi; Yu, Pu (Physical review. X, 2021)
The evolution between Fermi-liquid and non-Fermi-liquid states in correlated electron systems has been a central subject in condensed matter physics because of the coupled intriguing magnetic and electronic states. An effective pathway to explore the nature of non-Fermi-liquid behavior is to approach its phase boundary. In this work, we report a crossover from non-Fermi-liquid to Fermi-liquid state in metallic CaRuO3 through ionic liquid gating induced protonation with electric field. This electronic transition subsequently triggers a reversible magnetic transition with the emergence of an exotic ferromagnetic state from this paramagnetic compound. Our theoretical analysis reveals that hydrogen incorporation plays a critical role in both the electronic and magnetic phase transitions via structural distortion and electron doping. These observations not only help understand the correlated magnetic and electronic transitions in perovskite ruthenate systems, but also provide novel pathways to design electronic phases in correlated materials.